Hyperuricemia in Obese Children: Diagnostic Challenges, Pathophysiological Mechanisms, and Therapeutic Approaches - systematic review of current literature - Agnieszka Borończyk; Anna Bioły; Piotr Marcjasz; Agnieszka Buliszak; Monika Babczyńska; Karolina Kucia; Roksana Hrapkowicz; Piotr Zając (Quality in Sport)
Hyperuricemia in children with obesity is an increasingly common health issue, strongly associated with the development of various metabolic and cardiovascular diseases. It serves as a significant risk factor for conditions such as hypertension, type 2 diabetes, and chronic kidney disease. This study aimed to conduct a comprehensive review of the existing literature on the relationship between hyperuricemia and childhood obesity, adhering to the PRISMA guidelines for systematic reviews.